Active surface processes at Mahal Teglinos (Kassala, Eastern Sudan): Archaeological implications for an endangered protohistoric site in Sahelian Africa. (June 2022) - Costanzo, Stefano; Zerboni, Andrea; Manzo, Andrea
Highlights: The stratigraphic record of arid regions is prone to erosion. Erosion affects natural and anthropogenic sequences. Erosion is the reason of destruction of many archaeological sites in the Sahel. We reconstruct the effects of recent erosion on at Mahal Teglinos. Climate change seems to be exacerbating the destruction of archaeological sequences. Abstract: Erosion-related loss of archaeological record in arid lands is a foremost matter for researchers and local communities. A noteworthy case-study is represented by the Sahelian site of Mahal Teglinos (Kassala, Eastern Sudan), a secluded valley hosting rich Late Quaternary archaeological and sedimentary records that are undergoing irreversible damage. Here, we present the valley's geomorphological evolution, understanding the timing and effects of surface processes that are altering its topography and archaeological record. Today, hydric erosion is the main driver of soil displacement and loss, with the formation of rills, badlands and gullies being triggered, in turn, by hillside-channelled flash-floods and ground destabilization induced by human and animal agency. Stratigraphic analyses suggest the onset of the erosion may have started during the middle 1st millennium BCE. Nevertheless, contemporary plastic objects found within ancient-looking relict gullies spotlight a seemingly increasing erosional pace that may soon critically endanger the remaining archaeological record. Our geomorphological assessment of Mahal Teglinos represents a call for caution in regard to archaeological interpretations in geomorphologically active locations, as well as a warning of the threats faced by other known and still undiscovered Sahelian sites that are enduring similar climatic, geomorphological and anthropogenic constraints.